2014
DOI: 10.1136/archdischild-2012-303043
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol exposure in pregnancy and early childhood and development of childhood asthma: a systematic review and meta-analysis

Abstract: The association during early pregnancy exposure was highly variable between studies and exposure during infancy appears to be moderately confounded by respiratory tract infections. There is insufficient evidence to warrant changing guidelines on early life paracetamol exposure at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 51 publications
2
85
0
1
Order By: Relevance
“…Another recent meta-analysis of 11 observational cohort studies showed that the use of paracetamol, a common analgesic and antipyretic, during the first trimester increases the risk of asthma in children aged ≥5 years by 40% [81]. The mechanism of impact of this analgesic medication usually regarded as safe during pregnancy requires further study, particularly to discern the potential confounding issue of common respiratory tract infection.…”
Section: Gestational Exposuresmentioning
confidence: 99%
“…Another recent meta-analysis of 11 observational cohort studies showed that the use of paracetamol, a common analgesic and antipyretic, during the first trimester increases the risk of asthma in children aged ≥5 years by 40% [81]. The mechanism of impact of this analgesic medication usually regarded as safe during pregnancy requires further study, particularly to discern the potential confounding issue of common respiratory tract infection.…”
Section: Gestational Exposuresmentioning
confidence: 99%
“…For several years, it has been known that acetaminophen (paracetamol) in pregnancy and early childhood is associated with a significantly increased risk of the child developing asthma. This was confirmed in 2 studies 11,12 published in 2015 that also adjusted for respiratory infections, under the assumption that if the acetaminophen was taken to treat respiratory infection and fever, then the infection itself might explain the increased risk. What these studies showed was that both mothers who took acetaminophen during early pregnancy and in-fants who took acetaminophen were at significantly increased risk of developing asthma and that this risk was mitigated but not abolished when respiratory tract infections were accounted for.…”
Section: Asthma In Pregnancymentioning
confidence: 83%
“…What these studies showed was that both mothers who took acetaminophen during early pregnancy and in-fants who took acetaminophen were at significantly increased risk of developing asthma and that this risk was mitigated but not abolished when respiratory tract infections were accounted for. 11,12 The teratogenicity risk of asthma medications to the developing fetus was addressed in 2 studies. The EXPECT study 13 evaluated the risk of omalizumab (Xolair) in pregnancy, evaluating 191 pregnant women who were exposed to omalizumab during their first trimester.…”
Section: Asthma In Pregnancymentioning
confidence: 99%
“…There were 3 occasions, however, when the graph briefly leveled out, and 2 of these occasions were associated with a drop in acetaminophen sales because of public scares related to drug tampering. Prenatal use of acetaminophen has also been linked to an increased risk of asthma in the offspring, 12 and Becker and Schultz…”
Section: An Ecological Linkmentioning
confidence: 99%